Wheelchair foldable table / Muhammad Hadif Mohd Nasir … [et al.] - Mohd Nasir, Muhammad Hadif; Bidin, Fariz Hakim; Mohd Sukri, Muhammad Zuhair; Salman, Muhammad Shahrul Akhmal; Atan, Mohd Amirul (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
One of the most essential items in daily life is the table, serving various functions such as eating, working, and other activities. However, the lack of foldability in common tables necessitates significant storage space, rendering them impractical for individuals reliant on wheelchairs to enjoy their usefulness while on the move, thus hindering their mobility. The "Wheelchair with a Foldable Table" project aims to address this issue by providing a solution that enhances convenience and mobility for wheelchair users, enabling easy storage and transportation while prioritizing their unique needs and challenges.